Analisis segmenting, targeting, positioning dan bauran pemasaran (4P) terhadap usaha biskuit makanan pendamping asi (MP-ASI) berbasis mocaf (Modified cassava flour) - Nur Kartika Indah Mayasti; Arsy Priambudi; Lia Ratnawati; Cahya Edi Wahyu Anggara; Nurhaidar Rahman; Ashri Indriati; Yusman Taufik (AGROINTEK, 2024)
Complementary Food for Mother's Milk (MPASI) is a nutritious food that is given in addition to breast milk to infants aged 6 (six) months and over to achieve nutritional adequacy. MP-ASI products include porridge, pudding, biscuits, and others. Complementary food product development requires market research to be competitive in the market, one of which is mocaf-based MP-ASI biscuit products. This product has the advantage of being easy to carry, practical, and trains the strength of the baby's grip and bite. The raw material is mocaf based (gluten load). The purpose of this study is to analyze market aspects and design marketing strategies, namely segmenting, targeting, positioning (STP), and the 4P marketing mix (product, place, price, promotion). This type of research is descriptive qualitative research, and data collection techniques are interviews, observation, and documentation. Based on the results of the study it can be concluded that the product marketing strategy based on the 4P analysis (Product, Place, Promotion, and Price) is making new products in the form of gluten-free MP-ASI biscuits, marketing at minimarkets, conducting socialization and promotion at posyandu, and setting selling prices. IDR 14,000.